Not one inch : America, Russia, and the making of post-Cold War stalemate - Sarotte, Mary Elise, 1968- 1968- (The Henry L. Stimson lectures series, 2021)
Not one inch. With these words, Secretary of State James Baker proposed a hypothetical bargain to Soviet leader Mikhail Gorbachev after the fall of the Berlin Wall: if you let your part of Germany go, we will move NATO not one inch eastward. Controversy erupted almost immediately over this 1990 exchange-but more important was the decade to come, when the words took on new meaning. Gorbachev let his Germany go, but Washington rethought the bargain, not least after the Soviet Union's own collapse in December 1991. Washington realized it could not just win big but win bigger. Not one inch of territory needed to be off limits to NATO. On the thirtieth anniversary of the Soviet collapse, this book uses new evidence and interviews to show how, in the decade that culminated in Vladimir Putin's rise to power, the United States and Russia undermined a potentially lasting partnership. Prize-winning historian M. E. Sarotte shows what went wrong